World Power Conference (Berlin, Germany) reports and scrapbooks - World Power Conference 1930 : Berlin, Germany)
Reports of foreign power studies on the electrification of Afghanistan, Africa, Argentina, Australia, Austria, and Finland. Scrapbooks contain clippings from American newspapers relating to the conference.
Keywords: Electrification -- Afghanistan; Electrification -- Africa; Electrification -- Argentina; Electrification -- Australia; Electrification -- Austria; Electrification -- Finland; Electrification -- Congresses -- Germany -- Berlin